ฤทธิ์การต้านอนุมูลอิสระและฤทธิ์การยับยั้งแอลฟากลูโคซิเดสของสารสกัดจากเปลือกอบเชย - สุขเอม, จุฑามาส; ผลประไพ, ชนัญ; อุ่นทวี, ศรัญยู; จันทร, สุดาทิพย์ (Thai Journal of Science and Technology, 2020)
This study aimed to examine extraction yield, antioxidant activity, total phenolic content, and alpha-glucosidase inhibitory activity of cinnamon bark extracts for being used as an alternative for type 2 diabetes treatment including diabetic complications alleviation. In this experiment, powdered cinnamon bark was extracted by immersing in 95 % ethanol (EtOH), methanol (MeOH), ethyl acetate (EtOAc), and n-hexane (HEX) under various shaking periods. The results revealed that shaking cinnamon bark with MeOH for 48 h provided the highest extraction yield of 16.75±0.59 %w/w. However, the extracts obtained from shaking with EtOH, MeOH, and EtOAc, possessed approximately the similar high antioxidant activity. In addition, the IC50 values against DPPH radical of the extracts were not statistically different, as the values were found in a range of 2.36 - 5.47 µg/mL. The total phenolic content (TPC) of the ethanolic extracts gained from shaking for 36 and 48 h, expressed the TPC values of 108.53±0.00 and 118.86±2.24 mg GAE/g extract, respectively, while the methanolic extract gained from shaking for 48 h also expressed the TPC value of 116.28±0.00 mg GAE/g extract. Furthermore, the IC50 against alpha-glucosidase of two ethanolic and a methanolic extracts revealed the respective values of 34.82±0.25, 34.43±0.03, and 36.15±0.03 µg/mL, which were highly effective and insignificant differences. One-way analysis of variance also confirmed that the types of extraction solvent and shaking time could affect the extraction yield, antioxidant activity, total phenolic content, and alpha-glucosidase inhibitory activity. The results obviously supported that the 36-h shaken ethanolic extract could be potentially used for alleviating type 2 diabetes.